2021
DOI: 10.1109/jbhi.2021.3054592
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Classification of Cushing's Syndrome Using Retrospective Data

Abstract: Accurate classification of Cushing's Syndrome (CS) plays a critical role in providing the early and correct diagnosis of CS that may facilitate treatment and improve patient outcomes. Diagnosis of CS is a complex process, which requires careful and concurrent interpretation of signs and symptoms, multiple biochemical test results, and findings of medical imaging by physicians with a high degree of specialty and knowledge to make correct judgments. In this article, we explore the state of the art machine learni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…Isci S. и соавт. [ 10 ] впервые предложили способ дифференциальной диагностики различных форм эндогенного гиперкортицизма (БИК, синдром Иценко-Кушинга (СИК), субклинический гиперкортицизм) с использованием методов машинного обучения, основанный на данных 241 пациента и включивший 11 переменных-предикторов. Для создания прогностических моделей ученые применили различные методы машинного обучения, по результатам которых алгоритм случайного леса (Random Forest, RF) значительно превосходил прогностические способности других алгоритмов машинного обучения.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Isci S. и соавт. [ 10 ] впервые предложили способ дифференциальной диагностики различных форм эндогенного гиперкортицизма (БИК, синдром Иценко-Кушинга (СИК), субклинический гиперкортицизм) с использованием методов машинного обучения, основанный на данных 241 пациента и включивший 11 переменных-предикторов. Для создания прогностических моделей ученые применили различные методы машинного обучения, по результатам которых алгоритм случайного леса (Random Forest, RF) значительно превосходил прогностические способности других алгоритмов машинного обучения.…”
Section: Discussionunclassified
“…Для идентификации наилучшего алгоритма прогнозирования АКТГ-ЭС среди пациентов с АКТГ-зависимым эндогенным гиперкортицизмом применялась вложенная кросс-валидация с 5 внешними и 3 внутренними циклами (3x5 Nested Cross-Validation) по схеме, предложенной Isci S. и соавт. [ 10 ]. Данный подход обеспечивает более точную оценку ошибки обобщения (Generalization error) при одновременной оптимизации гиперпараметров и показал свою применимость в предметной области.…”
Section: обучение моделейunclassified
“…In particular, it is used in promoting treatments and improving prognosis for patients with Cushing's syndrome. A relevant study indicated that RF is the most suitable method for classifying the syndrome [31]. Regarding the high costs involved in the prediction of treatment fees for patients with asthma, the frequently used comorbidity portfolio design involves the recombination of comorbidities in different budgets, where the training for comorbidity portfolio design includes the training of RF prediction models [32].…”
Section: B Rfmentioning
confidence: 99%
“…Artificial Intelligence (AI), specifically ML, has shown exceptional promise in various fields, particularly in automating tasks and enhancing predictions. In the medical sphere, ML has contributed to more efficient diagnoses and treatment plans, and in certain areas, even surpassed human experts in diagnostic accuracy 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%